Implementation of Risk-Based Business Licensing Policy at the Investment and One-Door Integrated Services Department in Sintang Regency - Lestari, Reni Puji; Herawati , Netty; Arifin; Martoyo; Sudirman (Universitas Islam Negeri Raden Intan Lampung, 2026)
The implementation of risk-based business licensing through the Online Single Submission Risk-Based Approach (OSS-RBA) has become a key component of Indonesia’s public-service reform to improve regulatory efficiency, investment certainty, and digital governance. However, empirical evidence explaining how organizational capacity, policy interpretation, and policy application interact during local implementation remains limited. This study analyzes the implementation of OSS-RBA at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Sintang Regency using Jones and Baird’s policy implementation framework. A qualitative single-case study was employed. Data were collected from seven purposively selected participants through semi-structured interviews, non-participant observation, and document analysis, and analyzed using theory-informed thematic analysis with source and method triangulation. The findings indicate that OSS-RBA has strengthened administrative transparency, clarified licensing requirements based on business-risk classifications, and improved institutional arrangements for licensing services. Nevertheless, implementation remains constrained by limited human resources, uneven technical competence, interagency coordination challenges, unstable digital infrastructure, and varying digital capabilities among business actors. These conditions collectively influence organizational performance, policy interpretation, and service delivery. The study demonstrates that effective implementation depends on the interdependent relationship among organizational capacity, policy interpretation, and policy application rather than technological adoption alone. It refines the empirical application of Jones and Baird’s framework by illustrating how these dimensions interact within digitally mediated licensing services and provides practical insights for strengthening institutional capacity, adaptive coordination, and user-oriented digital services.